TRANSFORMASI DIGITAL PADA INDUSTRI PERBANKAN DAN DAMPAKNYA TERHADAP PELAYANAN NASABAH - Putri Fatimah; Nauval Khair; Moh. Hanafi; Achmarul Fajar (PT. Hasba Edukasi Mandiri, 2026)
Digital transformation has become one of the primary strategies adopted by the banking industry to address technological advancements and changing customer behavior. This study aims to analyze the implementation of digital transformation in the banking industry, examine its impact on customer service, and identify the benefits and challenges arising from the digitalization process. This research employs a qualitative method using a library research approach by collecting data from scientific journals, articles, books, official reports, and other credible sources. The findings indicate that digital transformation in banking is implemented through various innovations, including mobile banking, internet banking, artificial intelligence (AI), big data analytics, and digital customer onboarding. These technologies have generated positive impacts such as 24-hour service accessibility, improved transaction speed and efficiency, enhanced customer satisfaction, and reduced operational costs. However, digital transformation also presents several challenges, including cybercrime threats, personal data breach risks, high technology investment costs, human resource adaptation, and regulatory compliance. Therefore, optimization strategies are required through strengthening information security systems, improving digital literacy, developing customer-oriented service innovations, and fostering collaboration with financial technology companies to support successful digital transformation in the banking sector.